Geomorphologycal Domaines in Three Peaks State Park - Rio de Janeiro and its relationship with geological aspects - Freitas, Marcelo Motta; Eirado Silva, Luiz Guiherme; Tupinambá, Miguel (Sociedade & Natureza, 2017)
This paper proposes a classification of geomorphological features in the Três Picos State Park, in the mountainous region of Rio de Janeiro State, interpreted in the light of the long term evolution of weath ering and erosion on the weakness planes of geological substrate. The tectonic evolution, rock types and the structure are critical in the interpretation of land forms. In this study we defined eight geomorphological domains within the Park: South Escarpment; Três Picos-Frades-Caledônia granitic massive domain; Teresópolis granitic - gneiss massive domain; intermassif dissection domain; Macaé de Cima plateau domain; Hanging plateau’s boundaries domain; Fluvial plains domains (alluvial sediments) and Colluvial - alluvial ramps domains. These areas hold dynamics and historical developments associated with the erosive action of the long process limited by baselevels in several altitudes in specific lithologies and structures. The result of this evolution sets erosive processes that influence these landscapes to today, including generating risks in extreme situations.